1978
DOI: 10.1172/jci109215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic potassium loading on potassium secretion by the pars recta or descending limb of the juxtamedullary nephron in the rat.

Abstract: A B S T R A C T Recently we demonstrated potassium secretion by the pars recta or by the descending limb of the juxtamedullary nephron. The purpose of this present investigation is to study the effect of a chronic high-potassium intake on this phenomenon. Fractional reabsorption of water and sodium by the juxtamedullary proximal nephron was decreased when compared to that in normal hydropenic rats. There was a striking increase in the fraction of filtered potassium at the end of the juxtamedullary descending l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 29 publications
0
39
1
1
Order By: Relevance
“…The results of the present experiments demonstrate that an acute increase in ambient K concentration to ranges found in vivo (1) can produce a substantial reduction in VT and NaCl absorption across the MTALH of both the mouse and the rabbit. The effect is reversible and occurs under hypertonic and near isotonic conditions (Figs.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The results of the present experiments demonstrate that an acute increase in ambient K concentration to ranges found in vivo (1) can produce a substantial reduction in VT and NaCl absorption across the MTALH of both the mouse and the rabbit. The effect is reversible and occurs under hypertonic and near isotonic conditions (Figs.…”
Section: Discussionmentioning
confidence: 50%
“…Recent micropuncture experiments have demonstrated that K is recycled to the renal medulla (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to transepithelial bicarbonate transport, Good (25) has observed in the isolated rat MTAL perfused in vitro that increasing external potassium concentration from 4 to 24 mM had no effect on steady-state bicarbonate absorption; the latter result is, however, difficult to analyze with respect to the K+/HCO3 cotransporter described in the present study because potassium concentration was raised in both the perfusate and bath, which could have resulted in various direct, indirect, and possible opposite effects on basolateral bicarbonate transport and luminal proton secretion in the steady state. Selective large variations of the potassium concentration in the medullary interstitium, which may occur in vivo due to potassium recycling depending on the state of potassium balance (26)(27)(28), may modulate the K+/HCO3 cotransporter and thus bicarbonate absorption by the rat MTAL. The latter possibility could contribute to the acid-base disorders that are observed in a variety of pathologic conditions that include potassium imbalance (29).…”
Section: Discussionmentioning
confidence: 99%